Beliefs of Social Work Students in Israel about Wife-Beating: Are They Influenced by Their Patriarchal Ideology and Exposure to Violence in Their Families-of-Origin? - Malka, Menny (Victims & offenders, 2022)
Beliefs of Israeli undergraduate students of social work about wife-beating were examined, based on a combination of two theoretical frameworks, i.e., patriarchal ideology (as reflected in participants’ attitudes toward women and marital role expectations) and social learning theory (as reflected in their exposure to family violence during childhood). Self-administered questionnaires were filled out by a convenience sample of 542 students, from all three years of undergraduate studies in social work in seven academic institutions in Israel. The majority of participants were female (90.7%); 91.5% were Jews, and the remaining 8.5% were Arabs. The majority of participants expressed opposition to negative beliefs about wife-beating (e.g., opposed justifying wife-beating, expressed opposition for blaming battered women for husbands’ violence), and expressed willingness to help battered women. In addition, high percentages of the participants expressed willingness to hold violent husbands responsible for their behavior. Students’ liberal attitudes toward women and egalitarian expectations of marriage correlated significantly with most non-lenient beliefs about battered women and violent husbands. Nevertheless, participants’ exposure to family violence did not correlate significantly with these beliefs. The predictability of these beliefs by participants’ patriarchal ideology and exposure to family violence has been examined. The implications of the results for future research and theory development as well as for professional socialization are discussed.